2009
DOI: 10.1126/science.1171203
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Causes Frontostriatal Reorganization and Affects Decision-Making

Abstract: The ability to shift between different behavioral strategies is necessary for appropriate decision-making. Here, we show that chronic stress biases decision-making strategies, affecting the ability of stressed animals to perform actions on the basis of their consequences. Using two different operant tasks, we revealed that, in making choices, rats subjected to chronic stress became insensitive to changes in outcome value and resistant to changes in action-outcome contingency. Furthermore, chronic stress caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
582
1
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 748 publications
(631 citation statements)
references
References 28 publications
39
582
1
9
Order By: Relevance
“…Chronic stressor agents cause a decrease in the amount of labeled PNN + neurons both in the medial and orbital regions of the prefrontal cortex. Other studies had already demonstrated the effects of chronic stress on the morphology of pyramidal neurons, such as structural modifications on dendritic arborization and decrease in the number of dendritic spines [18,20], probably due to an increase in the number of excitatory amino acids (glutamate) induced by greater amounts of glucocorticoids in the bloodstream [50,56,63]. Chronic stress also increased the expression of genes that regulate neuronal metabolism and synaptic changes in glutamate receptors [10,73].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Chronic stressor agents cause a decrease in the amount of labeled PNN + neurons both in the medial and orbital regions of the prefrontal cortex. Other studies had already demonstrated the effects of chronic stress on the morphology of pyramidal neurons, such as structural modifications on dendritic arborization and decrease in the number of dendritic spines [18,20], probably due to an increase in the number of excitatory amino acids (glutamate) induced by greater amounts of glucocorticoids in the bloodstream [50,56,63]. Chronic stress also increased the expression of genes that regulate neuronal metabolism and synaptic changes in glutamate receptors [10,73].…”
Section: Discussionmentioning
confidence: 92%
“…Chronic stress also interferes with the function of the sympathetic nervous system and the HPA axis [10,14,52]. However, since several studies have demonstrated that animals adapt to the predictability of a single stressor agent [12,57], in our study we used different stressors in a non-predicable way [49,50,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current views suggest that repetitive exposure to drugs of abuse evolve from goal-directed behaviors into habit-based actions (37,38). We previously demonstrated that stress, associated with increased GC secretion, alters the structure of the corticostriatal loops and steers the development of instrumental behavior into habitual behavior (39). The present demonstration of GCinduced programming of the structure and function of the NAcc provide, on the other hand, new insights into the mechanisms that underlie the transfer of conditioned 15 behavior to instrumental behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Stress has been shown to bias decision-making strategies by reducing contributions of the prefrontal cortex (PFC) and encouraging habitual stimulus-response processes (Dias-Ferreira et al, 2009;Schwabe and Wolf, 2009). Specifically, learning the weather prediction task under stress induced by the cold pressor test has been associated with increased use of implicit, striatum-mediated strategies (Schwabe and Wolf, 2012).…”
Section: Introductionmentioning
confidence: 99%